SOSIALISASI STRATEGI PEMASARAN DAN PENDAMPINGAN UMKM UNTUK MENGEMBANGKAN USAHA MELALUI DIGITAL MARKETING - ifaq, haifaq; zein, yuhaneth; maulana, ikhsan; indriyawati, novi (Politeknik Negeri Sriwijaya, 2024)
Small and medium enterprises (MSMEs) usually want to generate quality leads and increase sales. Additionally, it faces the same obstacles as other business categories. However, currently, many small companies lack knowledge about online marketing, thus preventing them from expanding their product marketing. Digital marketing is the application of digital technology that establishes online channels to markets and contributes to marketing activities. Assistance for entrepreneurs, product design, and creation of NIB Business Identification Number) are the objectives of this study online marketing via social media, and product labeling activities in East Ketapang village. Using a community approach, training and mentoring are part of the study methodology. The activity stages are in the form of observations and surveys, outreach about marketing via social media, mentoring for entrepreneurship and graphic design, and mentoring for NIB creation. The results clarify the significance of business legitimacy and product marketing through digital marketing for a company. Of the 11 MSMEs products, there were several obstacles in assisting in making NIBs, such as 4 MSMEs who were not willing to make them because they included their Population Identification Number (NIK). This activity is carried out for business actors and teenagers for mentoring andÂ socialization.